3D printed geopolymer: An efficient support for immobilization of Candida rugosa lipase - dos Santos, Letícia Karen [UNESP]; Botti, Renata Fuss; Innocentini, Murilo Daniel de Mello; Marques, Rodrigo Fernando Costa [UNESP]; Colombo, Paolo; de Paula, Ariela Veloso [UNESP]; Flumignan, Danilo Luiz [UNESP] (Elsevier, 2021)
Lattice-shaped geopolymers were successfully prepared by Direct Ink Writing to act as carriers for the immobilization of Candida rugosa lipase (CRL). The supported biocatalyst was evaluated in the hydrolysis of waste cooking oil (WCO), a preliminary step for the production of biodiesel. The lattice samples presented total and open porosities of 57.2 vol% and 56.4 vol% respectively, bulk density of 0.924 ± 0.059 g/cm3, and true density of struts of 2.157 ± 0.014 g/cm3. The permeability coefficients (k1 = (9.05 ± 0.41) × 10−9 m2 and k2 = (3.64 ± 0.26) × 10−4 m) were consistently higher than those of typical enzymatic carriers. The geopolymer surface was successfully modified to allow the immobilization process by covalent bonding of CRL. The hydrolytic activity reached 847.7 ± 9.7 U/g. A free fatty acids content of 75 wt% was achieved from the hydrolysis of WCO, proving the efficiency of immobilization and the suitability of lattice-shaped geopolymers as support for biocatalysts.
Keywords: Direct ink writing; Geopolymer; Immobilization; Lattice biocatalyst carrier; Lipase